Munchie Food: Munchie people. Reversing the generational paradigm - Ceriani, Giulia (E|C, 2020)
We propose to take a closer look at an “exemplary text” for the Millennials: MUNCHIES, the food channel of VICE, a portal with a high rate of controversy and desecration. These are the questions: which semiosphere, how specific in comparison with the competitors? What discursive configurations? Which modalities and which systems of belief, which system of values? But above all: how to define, through the constructed recipient of an apparently dedicated and consecrated text, an age and perhaps custom target? What changes, what anticipations? Or what conventions? And again: how to interrogate images and texts to verify the existence or obsolescence, stereotypy or originality, of the most inflated segment of these years?